Green Marketing and Green Brand Equity: Moderating Role of Religion - Syeda Nazish Zahra Bukhari; Baleegha; Syed Asim Ali Bukhari (Journal of Religion and Society, 2026)
This study examines the impact of green marketing mix constructs, i.e., green product, green price, green place, green promotion physical evidence, and social media directly on green brand equity (GBE) and explores how these relationships are influenced under the moderating role of religiosity in the Pakistani context. The study is grounded in the Social Identity Theory (SIT techniques), the Theory of Planned Behavior (TPB), and the Stimulus-Organism-Response (S-O-R) paradigm and conceptualizes green marketing efforts as stimuli, GBE as organism and green purchase behavior as the response. Quantitative Design was used and survey data of 235 Pakistani consumers were collected using an online administered questionnaire taken from verified resources. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to study the hypotheses. This study revealed that green prices, physical evidence and green promotion help in the development of green brand equity, which in turn stimulates purchasers to buy green products while green product attributes, social media and green places did not have a direct effect. Also result showed green brand equity (GBE) is a strong predictor of GPB. The study also showed that religiosity has a selective moderating effect, enhancing the effect of some marketing signals, while having no effect on other marketing signals, thus supporting the view that religious values moderate the ways in which green marketing cues are processed and evaluated by consumers. Finally, the findings offer valuable insights for organizations doing business in religiously sensitive emerging markets by stressing the importance of transparent pricing, believable promotions, and verifiable certification and labeling to enhance green brand equity and support sustainable consumption. Keywords Green Marketing, Green Brand Equity, Religiosity, Green Product, Green Pricing, Green Promotion, Social Media